Identification of Disulfide-linked Dimers of the Receptor Tyrosine Kinase DDR1 - Abdulhussein, Rahim (American Society for Biochemistry and Molecular Biology, 2008)
Discoidin domain receptor 1 (DDR1) is a transmembrane receptor tyrosine kinase activated by triple-helical collagen. So far six different isoforms of DDR1 have been described. Aberrant expression and signaling of DDR1 have been implicated in several human diseases linked to accelerated matrix degradation and remodeling, including tumor invasion, atherosclerosis, and lung fibrosis. Here we show that DDR1 exists as a disulfide-linked dimer in transfected as well as endogenously expressing cells. This dimer formation occurred irrespective of its kinase domain, as dimers were also found for the truncated DDR1d isoform. A deletion analysis of the extracellular domain showed that DDR1 mutants lacking the stalk region failed to form dimers, whereas deletion of the discoidin domain did not prevent dimerization. Point mutagenesis within the stalk region suggested that cysteines 303 and 348 are necessary for dimerization, collagen binding, and activation of kinase function. The identification of DDR1 dimers provides new insights into the molecular structure of receptor tyrosine kinases and suggests distinct signaling mechanisms of each receptor subfamily.